Biomonitoring of Heavy Metal Air Pollution in Warsaw Using Two Moss Species Pleurozium schreberi and Sphagnum palustre - Ilieva-Makulec, Krassimira; Plichta, Paweł Dariusz; Sierakowski, Maciej (Studia Ecologiae et Bioethicae, 2022)
The aim of the study was to assess air pollution with heavy metals in Warsaw, on the basis of the concentrations of selected elements in moss samples. The active biomonitoring method (moss-bag technique) was applied using two moss species Pleurozium schreberi and Sphagnum palustre. Moss samples were collected in the Kampinos National Park, and the prepared moss bags were distributed and exposed on seven sites in Warsaw. The analysis of metals accumulated in mosses was performed twice in 2020, after two (August-September) and four months (August-November) of exposure. The concentrations of seven heavy metals (Cr, Cu, Pb, Ni, Fe, Cd and Zn) in the mosses were determined, using an Inductively Coupled Plasma Optical Emission Spectrometer (ICP OES). Our results showed a clear dependence of heavy metal accumulation in the mosses on the location of the exposition site and the exposure period. Both species of mosses were found to accumulate the most metals in the vicinity of pollutant emitters, such as the ArcelorMittal Warsaw smelter, exit roads or roads in the city with heavy traffic, petrol stations, or construction works. After 4 months of exposure, in both moss species, the highest increases in the concentrations were found for four elements: Cr, Pb, Ni and Cd. Higher concentrations of some heavy metals in the mosses in 2020, as compared to previous studies, indicate a negative influence of progressing urbanisation on air pollution in Warsaw.